2013
DOI: 10.3892/etm.2013.1176
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of superficial infantile hemangiomas with timolol: Evaluation of short-term efficacy and safety in infants

Abstract: Timolol has been demonstrated to be efficacious in the topical treatment of superficial infantile hemangiomas (IHs). We conducted a prospective study to evaluate the short-term efficacy and safety of timolol in the treatment of superficial IH in Chinese infants. From March to November 2012, 124 patients with superficial IHs were included in the prospective study. The patients were divided into two groups: treatment (101 patients, the timolol drops were administered on the surface of the lesions three times dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 9 publications
3
36
1
7
Order By: Relevance
“…Topical timolol has fewer side effects than systemic administration of β-blocker. 38 However, systemic absorption following topical application of timolol can occur, especially in young infants. Pruritus may occur at the application site.…”
Section: Managementmentioning
confidence: 99%
“…Topical timolol has fewer side effects than systemic administration of β-blocker. 38 However, systemic absorption following topical application of timolol can occur, especially in young infants. Pruritus may occur at the application site.…”
Section: Managementmentioning
confidence: 99%
“…26,27 One study comparing ophthalmic timolol and imiquimod reported no differences in effects. 28 Two studies using laser as a comparator reported mixed results: no differences in average overall improvement in 1 study comparing timolol and timolol plus laser modalities 30 and greater response to timolol in superficial IH, with greater response of mixed IH to timolol plus laser in another.…”
Section: Figurementioning
confidence: 99%
“…[19][20][21][22] One cohort study compared oral propranolol (2 mg/kg/day) and intralesional bleomycin (0.5 mg/kg) 23 ; and 1 RCT and 1 cohort study evaluated oral propranolol (2-3 mg/kg/day) and other β-blockers (1-4 mg/kg/ day). 24,25 Three cohort studies and 2 RCTs assessed topical timolol (0.5%) compared with placebo or observation or another agent, [26][27][28][29][30] and 1 RCT and 1 cohort study evaluated different steroids, including oral prednisone and intralesional triamcinolone. 31,32 Studies included a total of 1265 children with IH (ages ranging from 2 weeks to 9 years), and most were fair quality.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations